2018
DOI: 10.1166/jnn.2018.14338
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sulfobetaine-Based Block Copolymer as Stabilizer in Silver Nanoparticle Production and Catalytic Activity Studies

Abstract: A zwitterionic sulfobetaine-based diblock copolymer was successfully synthesized and used in the preparation and stabilization of Ag nanoparticles (AgNPs). For the related block copolymer, a precursor AB type diblock copolymer was synthesized via atom transfer radical polymerization by using a MPEG-based ATRP macroinitiator and 2-(N-dimethylamino)ethyl methacrylate (DMA) comonomer. Tertiary amine residues of PDMA blocks in poly(ethylene glycol) methyl ether-b-poly[2-(N-diethylamino)ethyl methacrylate] (MPEG-b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The styrene monomer was purified by passing through basic alumina (SI‐AL) column. Small diameter Au, Ag, and Pt nanoparticles were produced and characterized as reported in our previous study 37,38 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The styrene monomer was purified by passing through basic alumina (SI‐AL) column. Small diameter Au, Ag, and Pt nanoparticles were produced and characterized as reported in our previous study 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…NiSO 4 solution (0.20 M, 10.0 ml) was then added and stirred for 24 h. Then, 3.0 g of urea was dissolved in water (10.0 ml) and added to the reaction medium and stirred at 80 °C for 48 h. At the end of the reaction, the pH of the medium was around 12 due to urea decomposition and ammonia formation. The production of NiO/metal NPs hollow spheres was accomplished by adding 1.0 ml of Au (4.50 ± 1.1 nm), Ag (7.95 ± 1.4 nm), and Pt (3.80 ± 0.6 nm) nanoparticle dispersions, which we previously produced, together with the NiSO 4 solution 37,38 . The product was centrifuged three times at 5000 rpm and washed 3 times with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that particle size had an important effect on catalytic activity of AgNPs. The catalytic activity decreased with an increase on AgNPs diameter but increased with nanometal concentration 102 …”
Section: Applicationsmentioning
confidence: 96%
“…The catalytic activity decreased with an increase on AgNPs diameter but increased with nanometal concentration. 102…”
Section: Catalytic Activitymentioning
confidence: 99%